2015
DOI: 10.1007/s00405-015-3711-9
|View full text |Cite
|
Sign up to set email alerts
|

The European GWAS-identified risk SNP rs457717 within IQGAP2 is not associated with age-related hearing impairment in Han male Chinese population

Abstract: This study aimed to test the association between the European GWAS-identified risk IQGAP2 SNP rs457717 (A>G) and age-related hearing impairment (ARHI) in a Han male Chinese (HMC) population. A total of 2420 HMC subjects were divided into two groups [group 70+: >70 years (n = 1306), and group 70-: ≤70 years (n = 1114)]. The participants were categorised into case and control groups according to Z high scores for group 70- and the severity of hearing loss and different audiogram shapes identified by K-means clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…It is generally accepted that cross-population PRS is not a powerful approach and a comprehensive review of PRS published from 2008 to 2017 demonstrated this [ 31 ]. Furthermore, a previous attempt to replicate a SNP identified on a hearing loss GWAS of Europeans in a Han-Chinese sample was also unsuccessful [ 32 ]. That said, within the same Northern European (TwinsUK) or similar European populations, prediction was robust and we include the other populations for completeness, to add to the literature that cross-population prediction is not particularly useful.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that cross-population PRS is not a powerful approach and a comprehensive review of PRS published from 2008 to 2017 demonstrated this [ 31 ]. Furthermore, a previous attempt to replicate a SNP identified on a hearing loss GWAS of Europeans in a Han-Chinese sample was also unsuccessful [ 32 ]. That said, within the same Northern European (TwinsUK) or similar European populations, prediction was robust and we include the other populations for completeness, to add to the literature that cross-population prediction is not particularly useful.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the Finnish study was performed in an isolated population of the Saami using a small sample, so results may not be pertinent to the outbred Northern European sample of our work. Similarly, a study in a Han Chinese male sample investigating the relationship between IQGAP2 and ARHI did not show any significant association 46 .…”
Section: Discussionmentioning
confidence: 90%